Therapeutic benefit evidences for postural neck and shoulder pain via muscular perfusion and dynamic spinal imaging perspectives - Shyi-Kuen Wu; Jian-Guo Bau; Tony Tung-Liang Lin; Ying-Hsuan Chao; Mu-Ting Wang; Yu-Chen Lin; Li-Chieh Kuo (Technology and Health Care, 2026)
Abstract Objective Sustained postural loading is a common contributor to neck-shoulder pain, yet its effects on muscle microvascular function and cervical segmental motion are not fully understood. This study investigated changes in muscle microcirculation and cervical intervertebral mobility in individuals with postural neck-shoulder pain and examined the effects of therapeutic stretching. Methods Thirty asymptomatic participants and thirty with neck-shoulder pain were assessed using laser-Doppler flowmetry and videofluoroscopy to measure blood flow in the sternocleidomastoid (SCM), upper trapezius (UT), and masseter (MA) muscles and spinal motion, respectively. The patient group participated in an 8-week supervised stretching intervention. Results Compared to asymptomatic controls, patients with neck-shoulder pain showed 7.3%-11.2% lower blood volume and 5.8%-13.6% lower blood speed in target muscles. Post-intervention, significant improvements were observed in blood volume (SCM: 71.26 ± 9.00, UT: 75.80 ± 27.22, MA: 83.78 ± 19.26 au) and speed (SCM: 16.09 ± 4.75, UT: 17.65 ± 6.83, MA: 24.55 ± 10.58 au; all p < 0.05). Intervertebral flexion/extension mobility from C2/3 to C6/7 also significantly improved. Conclusions Alterations in muscle microcirculation may be associated with impaired cervical biomechanics in postural neck-shoulder pain. Combined assessment of local blood perfusion and intervertebral mobility may provide valuable insights into the underlying mechanisms and support the development of targeted rehabilitation strategies to patients experiencing postural neck-shoulder pain.